A Comprehensive Review of Low- and Zero-Residue Pesticide Methods in Vegetable Production - Tahseen Chikte; Tomas Kopta; Václav Psota; Javier Arizmendi; Mirosława Chwil (Agronomy)
Increasing demand for sustainable vegetable production is leading to low- and zero-pesticide farming practices. This review examines many strategies intended to lower pesticide use without impacting crop quality and production. The use of biopesticides, biological control, integrated pest management (IPM), and organic farming are some of the important techniques that are examined. This investigation also covers cutting-edge technology that improves the efficacy and efficiency of various techniques, such as robots, artificial intelligence (AI), and precision agriculture. A rigorous evaluation of the effects of pesticide residues on the environment and human health emphasises how crucial it is to use fewer pesticides. Market trends and customer preferences are considered, as well as the social and economic effects of implementing these strategies. The paper’s conclusion identifies obstacles to the general adoption of low- and zero-pesticide approaches and makes recommendations for future research topics to overcome these obstacles.